2019
DOI: 10.1038/s41598-019-51803-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fok1 VDR polymorphism with Vitamin D and its associated molecules in pulmonary tuberculosis patients and their household contacts

Abstract: Status of Fok I VDR polymorphism along with vitamin D, Vitamin D receptor (VDR), and cathelicidin levels in Tuberculosis (TB) patients compared to household contacts and implication of these findings in susceptibility to TB is not known. 150 active TB patients, 150 household contacts and 150 healthy controls were recruited from North Indian population. Fok1 VDR polymorphism was studied by polymerase chain reaction- restriction fragment length polymorphism (PCR-RFLP).VDR mRNA and protein levels were studied usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
(22 reference statements)
1
16
0
2
Order By: Relevance
“…Accordingly, results of vitamin D deficiency estimated by 25(OH) D levels from nine studies reported low levels among the TB patients. Six studies reported vitamin D deficiency levels of > 20 ng/ml [ 5 , 11 , 15 , 29 , 33 , 39 ] and three reported insufficient levels between 21–29 ng/ml [ 38 , 41 , 42 ]. Conversely, severe vitamin D deficiency as low as >10 ng/ml was reported by a study from Russia [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, results of vitamin D deficiency estimated by 25(OH) D levels from nine studies reported low levels among the TB patients. Six studies reported vitamin D deficiency levels of > 20 ng/ml [ 5 , 11 , 15 , 29 , 33 , 39 ] and three reported insufficient levels between 21–29 ng/ml [ 38 , 41 , 42 ]. Conversely, severe vitamin D deficiency as low as >10 ng/ml was reported by a study from Russia [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies measured circulatory LL-37 levels in both serum and plasma samples. Of these, six studies reported higher circulatory LL-37 levels in TB patients compared to the non-TB individuals [ 5 , 11 , 29 , 33 , 39 , 41 ]. Two studies found lower serum LL-37 levels in TB patients compared to non -TB individuals [ 38 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,15 Tuberculosis has been linked with vitamin D deficiency and VDR polymorphisms which make these populations particularly susceptible to the ailment. [16][17][18] Progression of TB in affected individuals has a strong correlation with serum vitamin D levels. 19 This may be explained by the bactericidal action of vitamin D against Mycobacterium tuberculosis such as reversal of mycobacterium tuberculosis-induced inhibition of phagosome maturation, which is an important element of progression of tu-berculosis.…”
Section: Vitamin D and Infectionmentioning
confidence: 99%
“…These naturally occurring polymorphisms are exclusively active in immune cells, offering a unique platform to study the immunomodulatory properties of VDR in a physiological context, without systemic vitamin D-related effects. Overexpression of VDR enhances T cell-driven inflammation in mice and associates with autoimmune arthritis in humans (8)(9)(10). These observations suggest that even highly localized VDR expression levels in inflammatory conditions, rather than 25(OH)D 3 availability, could be associated with a poor disease prognosis in autoimmune patients.…”
mentioning
confidence: 99%